Análisis del nivel de la cartera vencida de la empresa Vizcarra Hnos. Insumos Agrícolas agencia Ventanas en el año 2020 - Carriel Carrera, Ámbar Nahily (2021)
The report is based on the analysis of the company “VISCARRA HNOS”, the Ventanas agency, with the primary objective of studying the factors that have influenced the level of the overdue portfolio for the 2020 period; through the information obtained through the company "VISCARRA HNOS". The credits that the company has granted are at reasonable terms according to their needs, the values must be paid in harvests at the beginning of May. However, most of these terms are not carried out, therefore, accounts receivable is given, which are a main asset for the company; which provides us with the necessary information to determine what types of internal (management) and external (climatic) factors are affecting accounts receivable. The inductive methodology will be applied, this being the guided discussion strategy, so it begins with certain assumptions and reaches general conclusions. In addition, the interview technique will be applied to the main executives (legal representative and accountant).